The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/cge.12456
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of tooth agenesis in Japan: a population‐ and family‐based study

Abstract: Tooth agenesis is one of the most common congenital anomalies in humans. However, the etiology of tooth agenesis remains largely unclear, as well as evidence base useful for genetic counseling. Therefore, we estimated the prevalence and sibling recurrence risk, and investigated agenetic patterns systematically. Tooth agenesis was classified into two subtypes: hypodontia (one to five missing teeth) and oligodontia (six or more missing teeth). The prevalence of these two subtypes were 6.8% [95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
14
0
3
Order By: Relevance
“…[1][2][3] Isolated oligodontia can be a heritable developmental abnormality with a 0.1% prevalence. 4 It is often linked to a mutation in genes encoding transcriptional factors involved in early steps of odontogenesis (MSX1, PAX9, AXIN2, IRF6), or components of ectodysplasin signaling (EDA, EDAR, EDARADD) or Wnt signaling pathways (WNT10A, LRP5/6).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Isolated oligodontia can be a heritable developmental abnormality with a 0.1% prevalence. 4 It is often linked to a mutation in genes encoding transcriptional factors involved in early steps of odontogenesis (MSX1, PAX9, AXIN2, IRF6), or components of ectodysplasin signaling (EDA, EDAR, EDARADD) or Wnt signaling pathways (WNT10A, LRP5/6).…”
Section: Introductionmentioning
confidence: 99%
“…Tooth agenesis is classified into two subtypes according to the number of missing teeth: hypodontia (one to five missing teeth, excluding the third molar) and oligodontia (six or more missing teeth, excluding the third molar). Recently, we reported that the prevalences of these two subtypes in the Japanese population are 6.8% (hypodontia) and 0.1% (oligodontia) and that the sibling recurrence risks are 25.0% and 43.8%, respectively, suggesting that the severe phenotype, oligodontia, may be mostly transmitted in a dominant fashion [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Congenital tooth agenesis is one of the most common anomalies in human development, which is highly heritable and observed in the general population with racial/ethnic difference in prevalence of 0.08–0.16%. 1–3 It has been identified some homeodomain transcription factor cording genes as genetic causes of isolated tooth agenesis, such as MSX1 [OMIM 142983], 4 and PAX9 [OMIM 167416]. 5 In addition to these homeoprotein transcription factors, haploinsufficiency of WNT signaling-related molecules including wingless-type MMTV integration site family, member 10A ( WNT10A ) [OMIM150400], 6–8 the axis inhibitor 2 ( AXIN2 ) [OMIM 608015], 9 and low-density lipoprotein receptor-related protein 6 ( LRP6 ) [OMIM 616724] cause human tooth agenesis.…”
mentioning
confidence: 99%